Epitaxies of Ca-sulfates on calcite (CaCO3) I. Gypsum 010 on the calcite 10.4 form: epi-twins of gypsum induced by the calcite substrate. Issue 28 (30th June 2022) - Aquilano, D.; Bruno, M.; Cotellucci, A.; Pastero, L.; Ghignone, S.
Abstract : 3D-epitaxy of the 010 pinacoid of deposited gypsum on 10.4 calcite rhombohedron is described, in order to give a theoretical background to the replacement of calcite with gypsum both in the laboratory and by weathering in nature. Abstract : 3D-epitaxy of the 010 pinacoid of deposited gypsum (CaSO4 ·2H2 O) on the substrate 10.4 calcite rhombohedron is described, in order to give a theoretical background to the replacement of calcite with gypsum both in the laboratory and by weathering in nature. 2D-lattice coincidences are geometrically obtained from the matching of periodic bond chains (PBCs) running within the elementary slices facing towards the substrate/deposit interfaces. The epitaxy in the third dimension, perpendicular to the interfaces, has been verified as well, to establish if ad/absorption occurs (anomalous mixed crystals) at the calcite/gypsum contact. This research represents the reticular part of a wider program extended to the epi-interaction among the gypsum/calcite, gypsum/bassanite (CaSO4 ·1/2H2 O) and gypsum/anhydrite (CaSO4 ) couples.